The Place and Being in the Novel Takeoff Against Time: A Semiotic, Narrative, and Existential Reading - Emile , Emile (El Omda in Linguistics and Discourse Analysis, 2018)
The Abstract This study of the novel "Taking Off Against Time" is trying to enter the novelist's "Emily Nasrallah" world, revealing its vision to its world, its place, and the real existence it aspires to, by adopting the philosophical method of existentialism through the analysis of “Martin Heidegger” of the Dazin, as well as the Semiotic narrative approach by pausing at the place, its importance, its relation to the content of the novel, the interaction of the characters in it and the forming of its meaning. This is done in three parts: the first indicated that the spatial image came to serve the narrative and made it more realistic and credible, as well as able to describe, photograph and transfer facts and events and the evocation of places … While the second showed the movement of personality in the place where the self has faded and lived a kind of conflict between residence and departure, familiarity and strangeness, warmth and frost and between reassurance and anxiety ... What made the place the goal of the project; its features were characterized by desire, and lived self-struggle for his meeting. The third part illuminated on the meanings of authenticity and originality, where the place represented the role, the whole role the novelist wanted to narrate. It was all, the story, the identity, the existence, the self and the meaning of the latent and desired. Thus, the place, in this novel, emerged from its geographical framework, becoming a self-centered existential framework, a problem of being and existence ... And the novel became the novel of the place, its time, its people, its language, and the life that lives in its neighborhoods ... It is the novel of the return to authenticity, to being